Agricultural productivity and supply responses in Ghana - Nimo, Michael, Kwabi (2012)
The importance of Agricultural Supply Response (ASR) modelling cannot be over emphasised. Knowledge of its size provides a roadmap for designing a tailored agricultural policy based on suppliers’ responses to price and non-price incentives. In spite of its policy importance, limited amount of studies exist for Ghana. This study seeks to fill the gap and also sheds some light on how future agricultural policies in Ghana should be formulated.